PERANCANGAN MODEL INTERAKSI TANGAN VIRTUAL DALAM DUNIA AUGMENTED REALITY - Yuri Yudhaswana Joefrie (Foristek, 2013)
This research promoted the topic concerning the interaction technique using virtual hand in Augmented Reality environment (AR). AR uses tracker library that use marker to know the human gesture. With the kind of interaction i.e. manipulation of the model, manipulation of the street, button pressing, and duplicate the model, virtual hand could become an alternative in augmented reality’s environment. This study produces that to do all the kind of interaction stated above, we only need two finger to interact with. At the end, this virtual hand aimed to able to do such a basic interaction in the world of augmented reality.